ASSOCIATION BETWEEN DEMOGRAPHIC FACTORS AND ATTITUDE TOWARDS CREDIT CARD USAGE, AMONG THE HOUSEHOLDS IN KARAVEDDY DIVISIONAL SECRETARIAT IN JAFFNA DISTRICT - SRI LANKA - Athiyaman, T.; Subramaniam, V.A. (International Journal of Research -GRANTHAALAYAH, 2018)
Technological developments play a significant role in accelerating economic development of nations. One of the important evidence for the above statement is the payment system using the card. This payment instrument is called as credit card. The credit card, also referred to as "plastic money" represents a contemporary payment system in the modern world. It can be stated as a payment tool that provides to the people the possibility of purchasing needed goods or services, without making any payment at that moment of purchase, by allowing them to make such payment at a later time, without charging any additional financial burden.